Printing on fabric techniques with screens, stencils, inks, and dyes - Swearington, Jen (Lark Crafts, an imprint of Sterling Publishing, 2013)
"With a screen and squeegee in hand, you can transfer texture with wax, quickly apply simple stencils, or jump right into printing vivid, detailed images using photo emulsion. In this highly illustrated book, award-winning quilter and garment designer Jen Swearington covers all this and more. She also teaches print placement: learn how to layer prints, imply repeats to trick the eye, and plan precise repeats for yardage. Then explore the creative world of color with options exclusive to fabric--print with vibrant thickened dyes, bleach resists, and more. A wide variety of inventive projects in a range of sizes, from baby clothes to furniture, are sure to inspire your own print sessions." -- Provided by publisher